Homes that make us smart - Taylor, Alex; Harper, Richard; Swan, Laurel; Izadi, Shahram; Sellen, Abigail; Perry, Mark (Personal and Ubiquitous Computing, 2007)
In this article we consider what it should mean to build "smartness" or "intelligence" into the home. We introduce an argument suggesting that it is people who imbue their homes with intelligence by continually weaving together things in their physical worlds with their everyday routines and distinct social arrangements. To develop this argument we draw on four ongoing projects concerned with designing interactive surfaces. These projects illustrate how, through the use of surfaces like fridge doors and wall displays, and even bowl shaped surfaces, we keep in touch with one another, keep the sense of our homes intact, and craft our homes as something unique and special. Intelligence, here, is seen to be something that emerges from our interactions with these surfaces–seen in the thoughtful placement of things throughout the home's ecology of surfaces. IT for the home is thus understood less as something to be designed as intelligent and more as a resource for intelligence.